Self-Esteem dan Fungsi Psikoseksual pada Pasien Diabetes Melitus Tipe 2 - Nur Riyadi Sarjono; Ita Sulistiani; Mihrawaty S. Antu (Journal of Telenursing (JOTING), 2026)
This study aims to determine the relationship between self-esteem and psychosexual function in patients with type 2 diabetes mellitus in the Limboto Community Health Center (Puskesmas) in Gorontalo Regency. The method used was a quantitative cross-sectional approach. The results showed that the majority of respondents had low self-esteem (57 respondents (93.4%) and moderate psychosexual function (35 respondents (57.4%). Bivariate analysis revealed a significant relationship between self-esteem and psychosexual function, with a p-value of 0.000 (<0.05), indicating a strong, positive relationship. In conclusion, there is a significant relationship between self-esteem and psychosexual function in patients with type 2 diabetes mellitus, where higher self-esteem leads to better psychosexual function.   Keywords: Type 2 Diabetes Mellitus, Psychosexual Function, Self-Esteem